The Development of Climbing Mechanism for Cable Inspection Robot - Jordan, Hanshen; Christiand (Department of Mechanical Engineering Atma Jaya Catholic University of Indonesia, 2019)
For the maintenance of large cable-stayed bridge, cable inspection task using robot becomes an alternative method that is safer, easier and more efficient than a manual inspection. The method is believed to be superior than using drone or human in performing the cable inspection. Our research work focuses on the development of climbing mechanism for cable inspection robot. Our design of climbing mechanism enables the robot to climb on 115 mm cylindrical object, e.g. supporting cable or beam of the bridge. The mechanism can be controlled wirelessly to climb the cylindrical object with the diameter between 100 mm to 120 mm at maximum speed of 10 mm/s. The mechanism is powered by Li-Ion battery that is capable to reach 50 meter distance without the need of charging. The mechanism is also equipped with camera to take pictures of physical inspected objects, e.g. outer part of cable.